PERAN STRATEGI KOPING, KOMUNIKASI KELUARGA, DAN DUKUNGAN SOSIAL PADA PASANGAN YANG MENJALANI PERKAWINAN JARAK JAUH: SUATU STUDI LITERATUR - Muh Bukhari (Scientia Integritas Utama, 2022)
There are problems in the case of couples undergoing long-distance marriages, even though Marriage Law Number 1 of 1974 Article 1 has emphasized that marriage is an inner and outer bond of husband and wife to form a happy and eternal family based on God Almighty. Based on a literature study on functional structural theory, it is concluded that the quality of a marriage cannot be separated from good communication, coping strategies, and social acceptance and support for married couples who undergo long-distance marriages.